Critical Synthesis Package: American Board of Internal Medicine (ABIM) Peer Assessment - Matt J. Rustici (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the American Board of Internal Medicine (ABIM) Peer Assessment, and (2) a copy of the ABIM Peer Assessment instrument developed by Eric Holmboe, MD. The ABIM Peer Assessment is an 11-item instrument with responses recorded on a 9-point numerical rating scale with descriptive anchors. Higher scores indicate a more favorable assessment. The instrument was developed as a component of the ABIM re-certification process and is designed to assess practicing internal medicine physicians. Items assess ambulatory care skills, medical knowledge, management of multiple complex problems, problem solving, management of hospitalized patients, respect, integrity, psychosocial aspects of illness, compassion, responsibility and overall clinical skills. The instrument has demonstrated an acceptable generalizability coefficient (0.7) when 10-13 instruments are collected and seems to be minimally biased when peer evaluators are self-selected by the physician being evaluated. The instrument attempts to provide feedback to physicians from peers to help guide self-improvement plans and does not have any established minimum competency scores. In one study, scores of 100 practicing physicians were positively correlated to evaluations from residency directors but there is limited supporting data correlating scores on the instrument to other measures of physician competence.